High-order harmonic generation from ultrafast matter Talbot effect - Plaja Luis; García-Cabrera Ana; Hernández-García Carlos (EPJ Web of Conferences, 2024)
High-order harmonic spectroscopy is a robust method for probing electron dynamics under the influence of a driving field, capturing phenomena as brief as attoseconds. It relies on the extreme non-linear process of high-harmonic generation (HHG), where intense laser pulses are directed at a material, causing it to emit high-energy photons in harmonics of the laser frequency. In this contribution we explore the possibility to generate high-order harmonics from low-dimensional crystalline solids driven under grazing incidence. We demonstrate that, in this unconventional geometry, the electron wavefunction is ejected from the solid and, subsequently, redirected to it to generate harmonics. Most appealingly, we show that the crystal’s periodicity imprinted in the electron’s wavefunction introduces a revival dynamics closely connected with the matter temporal Talbot effect. These Talbot oscillations are ultrafast (< femtosecond) and leave a distinct signature in the high-frequency harmonic spectrum, in the form of structures extending beyond the main spectral cutoff.